Design and Educational Application of a Dual-MCU-Based Hardware Kit for IoT Security Practice - Kim, Dong-won (International Journal of Online and Biomedical Engineering (iJOE), 2025)
The proliferation of Internet of Things (IoT) devices has escalated cybersecurity threats, demanding practical, hands-on education for security professionals. However, traditional lecture-based learning and software-only simulations often fail to provide an immersive experience with hardware vulnerabilities. To address this gap, we designed and developed the “Hacker Board,” a novel educational hardware kit featuring a dual-MCU architecture that enables simultaneous attack and defense exercises on a single board. The kit is modular, supporting various IoT communication protocols such as IR, RF, RFID, and CAN. We implemented a pedagogical model combining flipped learning with Bloom’s Taxonomy and conducted a three-year case study (2022–2024) with undergraduate information security students to evaluate its effectiveness. A mixed-method approach was used, collecting quantitative survey data on student satisfaction, interest, and engagement, alongside qualitative interview data. The findings show consistently high student satisfaction (average 4.47/5.0), interest, and engagement, with scores trending upward over the three years. Qualitative feedback confirmed that the hands-on, hardware-based labs significantly enhanced students’ practical skills and learning immersion. This study concludes that the Hacker Board, coupled with a structured pedagogical model, serves as a promising and validated tool for overcoming the limitations of conventional cybersecurity education and provides a replicable framework for hands-on IoT security training.